PEDAGOGICAL TECHNOLOGY BASES FOR THE FORMATION OF CREATIVE PERSONALITY IN VOCATIONAL EDUCATION - Nozim Khusanov, Shahlo Nurullaeva, Nozima Kuvatova, Viloyat Begimkulova, Klara Akhmetova (International Journal of Advanced Science and Technology, 2020)
The pedagogical technology foundations of the formation of the teacher’s creative personality are considered taking into account the pedagogical aspects and urgent problems of the formation of a professional. The information-integration approach is defined as a theoretical basis. It also defines the principles of training teachers as representatives of the socionomic sphere of activity. The elements of the formative experiment on the application of technologies for the formation of the creative personality of the teacher in vocational education are indicated.